2001
DOI: 10.1093/bja/86.1.77
|View full text |Cite
|
Sign up to set email alerts
|

Intrathecal midazolam increases the analgesic effects of spinal blockade with bupivacaine in patients undergoing haemorrhoidectomy

Abstract: In the present double-blind study we aimed to evaluate the postoperative analgesic effects of intrathecal midazolam with bupivacaine following haemorrhoidectomy. Forty-five patients were randomly allocated to one of three groups: the control group received 1 ml of 0.5% heavy bupivacaine plus 0.2 ml of 0.9% saline intrathecally, group BM1 received 1 ml of 0.5% bupivacaine plus 0.2 ml of 0.5% preservative-free midazolam and group BM2 received 1 ml of 0.5% bupivacaine plus 0.4 ml of 0.5% midazolam. Time to first … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
79
2
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 110 publications
(94 citation statements)
references
References 12 publications
10
79
2
1
Order By: Relevance
“…This could be due to a local anesthetic property of midazolam and its synergistic action with that of local anesthetics. [10][11][12] The onset of motor block was found to be faster than the onset of sensory block in both groups. Winnie et al 16 observed this also, and attributed this to the Group B = were administered bupivacaine; Group BM = were administered bupivacaine and midazolam.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…This could be due to a local anesthetic property of midazolam and its synergistic action with that of local anesthetics. [10][11][12] The onset of motor block was found to be faster than the onset of sensory block in both groups. Winnie et al 16 observed this also, and attributed this to the Group B = were administered bupivacaine; Group BM = were administered bupivacaine and midazolam.…”
Section: Discussionmentioning
confidence: 84%
“…[10][11][12] Gulec et al 17 found that a bupivacaine and midazolam combination prolonged postoperative analgesia compared to a bupivacaine-morphine combination when administered caudally. Nishiyama et al 11 added midazolam to a continuous epidural infusion of bupivacaine and observed improved analgesia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Local anaesthetics alone for subarachnoid block provide good operative conditions but have shorter duration of postoperative analgesia. So various drugs like opioids [7], epinephrine [8], neostigmine [9], magnesium [10], midazolam [11], ketamine [12], and clonidine [13] have been used as adjuvant to intrathecal local anaesthetics to achieve quick, dense and prolonged block, but the results were associated with side effects.…”
Section: Discussionmentioning
confidence: 99%
“…Diverse classes of drugs such as opioids [7], epinephrine [8], neostigmine [9], magnesium [10], midazolam [11], ketamine [12], and clonidine [13] have been added to intrathecal local anaesthetics in an attempt to prolong analgesia and reduce the incidence of adverse events.…”
mentioning
confidence: 99%